Covalently bonded 3D rebar graphene foam for ultrahigh-areal-capacity lithium-metal anodes by in-situ loose powder metallurgy synthesis. (March 2020) - Tang, Yu; Sha, Junwei; Wang, Ning; Zhang, Rui; Ma, Liying; Shi, Chunsheng; Liu, Enzuo; Zhao, Naiqin
Abstract: A free-standing covalently bonded CNTs/graphene foam (LPM-3D rebar GF) is developed by using an in-situ loose powder metallurgy templates method for high-performance dendrite-free Li metal anodes. The LPM-3D rebar GF possesses a macroporous structure with interconnected porous pipelines. The homogeneously dispersed CNTs can induce an in-situ growth for covalently bridging graphene sheets, resulting in the increase of electrical conductivity, structural stability, and active Li nucleation sites . With the guidance of CNTs, Li metal deposit preferentially on the junctions of CNTs and graphene to achieve a uniform deposition and avoid the formation of Li dendrites effectively, which is verified by both experiments and first-principle calculations. As the anode of Li metal battery, the LPM-3D rebar GF shows outstanding cycling stability even at 20 mA cm −2 for 20 mA h cm −2 . Notably, this anode can still operate 90 cycles at 30 mA h cm −2 with a Coulombic efficiency (CE) of >98%. These properties indicate promising prospects of LPM-3D rebar GF as a new and dendrite-free anode with large areal capacity for high-performance Li metal batteries, and in other fields requiring 3D carbon monoliths including fuel cells and sodium-ion batteries. Graphical abstract: Image 1 Highlights: Covalently bonded CNTs/graphene foam (LPM-3D rebar GF) wasdeveloped through an in-situ loose powder metallurgy approach. Li was uniformly deposited under the guidance of CNTs by nucleating preferentially at the covalent junctions. The LPM-3D rebar GF shows excellent performance at high current density of 20 mA cm −2 for areal capacity of 20 mA h cm −2 .